SURGICAL TREATMENT OF PATIENTS WITH MASSIVE INTRAPERITONEAL RECURRENCE OF COLORECT AL CANCER, COMPLICATED BY INTRA-ABDOMINAL HYPERTENSION SYNDROME (CLINICAL OBSERVATION) - D. V. Sidorov; M. V. Lozhkin; L. O. Petrov; Y. A. Solovyov; A. A. Kostin (Исследования и практика в медицине, 2016)
Complications of tumor in patients with colorectal cancer are well known — a bowel obstruction, bleeding, perforation, tumor, liver failure, etc. Less common is a complication of massive intra-abdominal recurrence of colon cancer as the abdominal kompartment-syndrome or abdominal hypertension — rapid or gradual increase in intra-abdominal pressure to the further development of multiple organ failure. In this article we present a clinical case of surgical treatment of patients with metastatic colorectal cancer, complicated by intra-abdominal hypertension syndrome.